Pentingnya Desain Interior terhadap Kenyamanan Pengunjung Perpustakaan - Afrina, Cut; Rasyid, Saifuddin; Nazira, Hanifa; Oktaviani, Annisa; Yoelanda, Aqli Mazikra; Syukrinur, Syukrinur; Elvi, Elvi (Jurnal Pustaka Ilmiah, 2023)
Interior design is very important and needs to be considered when building a library. Efforts to present a library interior design that meets the needs and comfort of library visitors requires good understanding and planning. Library interiors that combine aesthetic values will affect the use of library services for users. This study uses the method of literature study or literature review through scientific concepts that discuss library science from several library journals and interior design. The research develops the main issues on how interior design can affect the comfort of library visitors and how to develop a good library interior design. The aim of the research is to find out how interior design affects the comfort of library visitors. This research is expected to be useful for library development and facilitate planning in the library.